GE_GERICHTE A/716/2014 vom 29. Juli 2014 - GE Cour de justice (2014)
FORMATION(EN GÉNÉRAL) ; ÉCOLE OBLIGATOIRE ; ÂGE ; LIMITE D'ÂGE ; EXCEPTION(DÉROGATION) | Cst.9; Cst.29.al2; Harmos.5; CICS.2; CSR.1; CSR.2; CSR.3; CSR.4; LIP.11